2019
DOI: 10.1089/neu.2018.6360
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Mild Traumatic Brain Injury Recruited from Both Hospital and Primary Care Settings: A Controlled Longitudinal Magnetic Resonance Imaging Study

Abstract: With an emphasis on traumatic axonal injury (TAI), frequency and evolution of traumatic intracranial lesions on 3T clinical magnetic resonance imaging (MRI) were assessed in a combined hospital and community-based study of patients with mild traumatic brain injury (mTBI). The findings were related to post-concussion symptoms (PCS) at 3 and 12 months. Prospectively, 194 patients (16–60 years of age) were recruited from the emergency departments at a level 1 trauma center and a municipal outpatient clinic into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 55 publications
3
53
1
Order By: Relevance
“…Both 3-T scanning 31 and SWI 1,13 increase the sensitivity for lesion detection, which could possibly have led to both higher occurrence and grades of TAI. On the other hand, a recent study from our research group using both 3-T scanning and SWI within 72 hours found TAI lesions in only 6% of patients with mild TBI, 8 compared to 74% of patients with moderate and severe TBI in the current study. Hence, 1.5-T scanning and T2*GRE may be sufficiently sensitive to detect visible TAI lesions in moderate and severe TBI.…”
Section: Study Strengths and Limitationscontrasting
confidence: 93%
“…Both 3-T scanning 31 and SWI 1,13 increase the sensitivity for lesion detection, which could possibly have led to both higher occurrence and grades of TAI. On the other hand, a recent study from our research group using both 3-T scanning and SWI within 72 hours found TAI lesions in only 6% of patients with mild TBI, 8 compared to 74% of patients with moderate and severe TBI in the current study. Hence, 1.5-T scanning and T2*GRE may be sufficiently sensitive to detect visible TAI lesions in moderate and severe TBI.…”
Section: Study Strengths and Limitationscontrasting
confidence: 93%
“…The cohort and magnetic resonance imaging (MRI) follow-up have been described in detail previously. 12,13 All data were handled in accordance with the STROBE checklist ( Supplementary Fig. S1).…”
Section: Ethics Participants and Recruitmentmentioning
confidence: 99%
“…The clinical scans were read by an experienced neuroradiologist according to predefined criteria as described in a previous publication. 13…”
Section: Magnetic Resonance Imaging Protocolmentioning
confidence: 99%
“…Intracranial traumatic findings were obtained from Magnetic Resonance Imaging (MRI), performed within 72 h. MRI was performed on a 3.0 Tesla Siemens Skyra system (Siemens Healthcare, Erlangen, Germany) with a 32-channel head coil. The MTBI was classified as uncomplicated if there were no intracranial traumatic lesions on MRI, as described in detail previously ( 23 ). All patients in the present study underwent MRI.…”
Section: Methodsmentioning
confidence: 99%
“…All patients in the present study underwent MRI. In addition, CT was performed in the majority of the patients, but none of the patients had intracranial findings on CT that were not detected on MRI (23).…”
Section: Participantsmentioning
confidence: 99%